Abnormal Exercise Test or CVD History on Weight Loss or Fitness: The Look AHEAD Trial. Issue 12 (2020) - Jakicic, John M.; Horton, Edward S.; Curtis, Jeffrey M.; Killean, Tina M.; Bray, George A.; Cheskin, Lawrence J.; Johnson, Karen C.; Middelbeek, Roeland J. W.; Pi-Sunyer, F. Xavier; Regensteiner, Judith G.; Ribisl, Paul M.; Wagenknecht, Lynne; et al.
ABSTRACT: Purpose: Obesity and type 2 diabetes are associated with an increased risk of cardiovascular disease (CVD), and the combination of weight loss and increased physical exercise are commonly recommended to reduce CVD. This study examined whether people with obesity and type 2 diabetes with an abnormal graded exercise tolerance test (GXT) or a history of CVD would have less success in achieving weight loss and improved fitness compared with adults without these conditions. Methods: The Look AHEAD Study examined whether an intensive lifestyle intervention (ILI) compared with diabetes support and education (DSE) reduced cardiovascular events in adults with overweight/obesity and type 2 diabetes. Participants underwent a baseline maximal GXT and provided medical history data. Weight loss and fitness change were examined in 5011 participants over 4 yr in those with or without an abnormal baseline GXT and/or history of CVD. Results: After 4 yr, weight loss in both ILI and DSE were significantly greater in those without a history of CVD than in those with a CVD history (6.69% vs 5.98%, P = 0.02, in ILI and 0.73 vs −0.07% (weight gain), P = 0.01, in DSE). Likewise, those without a history of CVD experienced greater improvements in fitness in both ILI and DSE relative to those with a history of CVD. Having an abnormal GXT at baseline did not affect weight loss or fitness. Conclusions: A history of CVD at baseline modestly lessened weight loss and fitness changes at 4 yr, whereas having any abnormality on the baseline GXT did not affect these outcomes. Thus, weight loss and improved fitness are achievable in adults with a history of CVD or ECG abnormalities.